2014
DOI: 10.3810/hp.2014.04.1106
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Therapeutic Goal Attainment in Patients With Concomitant Hypertension and Dyslipidemia

Abstract: These variations in therapeutic goal attainment in patients with concomitant hypertension and dyslipidemia across different BMI groups suggest that future research is needed to determine the underlying reasons for these disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
3
11
0
1
Order By: Relevance
“…These results reflected a gender difference in the likelihood of target attainment: women were less likely to meet guidelinerecommended targets than men with a high WC or WtHR. This is partly consistent with the findings of several previous studies 9,23,26,27 , which reported that a higher proportion men achieved targets than women. However, these previous studies did not report that women with abdominal obesity were less likely to achieve targets.…”
Section: Discussionsupporting
confidence: 94%
“…These results reflected a gender difference in the likelihood of target attainment: women were less likely to meet guidelinerecommended targets than men with a high WC or WtHR. This is partly consistent with the findings of several previous studies 9,23,26,27 , which reported that a higher proportion men achieved targets than women. However, these previous studies did not report that women with abdominal obesity were less likely to achieve targets.…”
Section: Discussionsupporting
confidence: 94%
“…We identified sex disparities in achievement of CV treatment targets that are consistent with those seen in other cohorts [8][9][10]. Following publication of CV disease prevention guidelines specific to women [11], improved awareness of CV risk [12] and a one-third drop in age-adjusted death rates from coronary heart disease have been documented [13,14]; however, CV disease still outranks cancer, chronic lower respiratory disease, Alzheimer's disease and accidents for cause of death [15], and CV death rates in women aged 35-54 years are rising, presumably related to increasing rates of diabetes and obesity [14].…”
Section: Discussionsupporting
confidence: 71%
“…This was consistent with several previous studies conducted on patients with concomitant hypertension and dyslipidaemia, which reported BP goal attainment rates of 15%-54%. (1)(2)(3)15,16) Studies conducted in patients with isolated hypertension or dyslipidaemia had also shown that, even among patients who were treated, less than half reached their relevant therapeutic goal. (8) In patients with hypertension, it is critical to control not only BP, but also other cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Hypertension and dyslipidaemia are both independently associated with coronary heart disease (CHD), and the presence of both conditions concomitantly presents an additive risk of cardiovascular events. (2,3) The Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure (JNC 7) (4) and the European Society of Hypertension-European Society of Cardiology guidelines for the management of arterial hypertension (5) show that even small elevations above blood pressure (BP) goals increases the likelihood of developing a cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation